Thermal expansion of chromium-rich iron-based or iron/nickel-based alloys reinforced by tantalum carbides - Berthod, P.; Aranda, L.; Hamini, Y. (Фізико-хімічна механіка матеріалів, 2011)
Six alloys reinforced by TaC carbides based on iron (ferritic) or both iron and nickel (austenitic) were studied in thermal expansion between 100 and 1200°C for two microstructure orientations. The heating, isothermal and cooling parts of the dilatometry curves were characterized. The thermal expansion of the ferritic alloys is less important than that of the austenitic alloys. A compressive deformation of the matrix subjected to stresses applied by the carbides network was observed. The importance of this phenomenon seems depending more on the matrix nature than on the microstructure orientation. Досліджено шість сплавів на основі заліза (феритні та аустенітні) і нікелю, зміцнені карбідами TaC, та їх термічне розширення в інтервалі 100...1200°C для двох мікроструктурних орієнтацій. Проаналізовано ізотермічну та охолоджувальну ділянки на дилатометричних кривих. Термічне розширення феритних сплавів виражене не так чітко, як аустенітних. Стискальні деформації матриці призводять до напружень, які поширюються на колонії карбідів. Важливість цього явища вбачається у впливі фази матриці на мікроструктурні особливості сплаву загалом. Исследовано шесть сплавов на основе железа (ферритные и аустенитные) и никеля, упрочненных карбидами ТаС, и их термическое расширение в интервале 100... 1200°C для двух микроструктурных ориентаций. Проанализированы изотермический и охлаждающим участки на дилатометрических кривых. Термическое расширение ферритных сплавов выражено менее четко, нежели аустенитных. Сжимающие деформации матриц обуславливают напряжениям, которые распространяются на колонии карбидов. Важность этого явления видится во влиянии матричной фазы на микроструктурные особенности сплава в целом.